Obstructive Sleep Apnoea/Hypopnoea Syndrome and Hypertension - Al-Abri, Mohammed A (Sultan Qaboos University Medical Journal, College of Medicine & Health Sciences, 2008)
The obstructive sleep apnoea/hypopnoea syndrome (OSAHS) is a common disorder, affecting around 2–4% of the middle-aged population. There is a strong association between OSAHS and hypertension, based on animal, large epidemiological and interventional studies. The epidemiological studies have shown a dose-response relationship between apnoea/hypopnoea index (AHI) and the risk of developing hypertension. Different mechanisms may have a role in the process of elevated blood pressure in OSAHS. Sympathetic activity is increased in OSAHS patients during sleep and wakefulness. This increase in sympathetic activity is probably due to activation of baroreflexes and chemoreflexes by frequent arousals and hypoxaemia a result of apnoea or hypopnoea events. Continuous positive airway pressure (CPAP) has been shown to reduce sympathetic stimulation and blood pressure in OSAHS patients. Altered endothelial function may also have a role in the pathogenesis of hypertension in OSAHS subjects. Reduction of nitric oxide (NO) production and increase in the formation of free radicals may be responsible for the impairment of the vasodilatation of micro-vasculature in these subjects as a result of hypoxaemia. It has been shown that effective CPAP therapy has a reversible effect on endothelial dysfunction.